ChemInform Abstract: Functionalized Hexagonal Boron Nitride Nanomaterials: Emerging Properties and Applications. Issue 37 (August 2016) - Weng, Qunhong; Wang, Xuebin; Wang, Xi; Bando, Yoshio; Golberg, Dmitri
Abstract: Review: 205 refs.